Effect of microbial biofertilizers on the agronomic characteristic of the plant and fruit quality of xcat´ik pepper (Capsicum annuum L.) - Gamboa-Angulo, Julio Jacobo; Ruíz-Sánchez, Esaú; Alvarado-López, Carlos Juan; Gutiérrez-Miceli, Federico; Ruíz-Valdiviezo, Víctor M.; Medina-Dzul, Kati Beatriz (REVISTA TERRA LATINOAMERICANA, 2020)
Xcat´ik (Capsicum annuum L.) is the second most consumed pepper in the Yucatan Peninsula, after habanero pepper. The microbial biofertilizers are a feasible option to integrate into production systems to decrease the use of chemical fertilizers. The objective of this work was based on the evaluation of the effect of the application of Bacillus subtilis, Trichoderma harzanium and a microbial consortium on the agronomic characteristics of the plant and fruit quality of xcat´ik pepper. The experiment was conducted under greenhouse conditions through a completely randomized blocks experimental design with four replicates. According to the results, it was found that the application of B. subtilis significantly increased plant height, while the application of B. subtilis and T. harzanium increased root volume. Statistical differences in the lipid and protein contents in fruits of plants biofertilized with T. harzanium were observed, and greater amounts of phosphorous accumulate in the fruits of plants treated with B. subtilis and T. harzanium.